Peluang Dan Tantangan Penerapan Prinsip Syariah Dalam Operasionalisasi Koperasi Merah Putih - Nurhayati, Siti; Nurjamil, Nurjamil; Muhammad Iqbal, Eka (Universitas Koperasi Indonesia, 2025)
The implementation of Sharia principles in Koperasi Merah Putih presents significant opportunities to enhance member trust, expand access to Islamic financing, and strengthen governance grounded in fairness and transparency. This study identifies critical challenges, including regulatory disharmony, limited literacy in Sharia contracts, insufficient capacity of Sharia Supervisory Boards, and heightened managerial and financing risks during the transition phase. The analysis reveals that successful implementation requires regulatory harmonization, capacity building for human resources, optimization of Sharia supervisory functions, and integrated risk management. These findings provide strategic insights for developing a sustainable cooperative model that fully embodies Sharia principles in both form and substance. Keywords: Capacity Building, Cooperative Governance, Regulatory Harmonization, Sharia Compliance, Transition Risk